Characterization of a proposed quarry site using multi-electrode electrical resistivity tomography - John Stephen Kayode,; Mohd Hariri Arifin,; Mohd Nawawi, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This research focuses on the delineation of subsurface basement granitic structures suitable for engineering construction materials for the sitting of quarry industry in the area. The key objective of the study was to locate and delineate the depths of burial to the subsurface granite rock bodies and the regolith thickness overlain the bedrock unit. 14 resistivity profile lines with a surveyed length of 200 m and electrode spacing of 5 m, were carried out with the application of electrical resistivity tomography software, to image the subsurface structural units around this area, utilizing pole-dipole electrode configurations method towards assisting the Engineers in obtaining information on the subsurface geological features in this part of the Peninsula Malaysia. The focus is on characterizing engineering construction materials suitable for sitting the quarry industry, determination of the longitudinal conductance and coefficient of anisotropy of subsurface lithological units that determines the competency of the bedrock underneath the area from the geoelectric parameters obtained through the interpretations of the RES2DINV ERT images. The depth of bedrock unit as delineated from the results ranged from about 5 m to 100 m while the resistivity values recorded was greater than 6000 Ω-m in most of the profiles. Groundwater bearing channels that would serve the factory needs was delineated alongside the granitic rock unit. These results make the subsurface granitic bedrock unit to be adjudged competent and suitable enough as quarry construction materials for sitting the factory in the area.